Dynamics of macronutrients in Coffea canephora genotypes with potential for use as rootstock - Carvalho, João Paulo Felicori; Carvalho, Gladyston Rodrigues; Ferreira, André Dominghetti; Rezende, Juliana Costa de; Dias, Rodrigo Elias Batista de Almeida; Carvalho, Alex Mendonça de (Coffee Science - ISSN 1984-3909, 2015)
The cultivate Apoatã 2258 (Coffea canephora) has been used as a rootstock cultivar of Coffea arabica. However, due to the wide availability of genetic resources found in different regions of the country, there is a vast field to be explored in the research of new genotypes to be used as rootstock. The choice of these materials should be based in combination with the graft and adaptation to the ecosystem where it is inserted.Thus, this study aimed at evaluating the efficiency of absorption, translocation and use of macronutrients in genotypes of C. canephora, to determine their potential of use as rootstocks. Two experiments were carried out in a period of five months in a greenhouse, using the process of hydroponics, growing in pots containing nutrient solution. In the experiment 1 (E1) , treatments included five C. canephora genotypes (Apoatã IAC3598-3B, Apoatã IAC3597-1A, Apoatã IAC3599-2A-1A, Apoatã IAC3598 and Apoatã IAC3597-9B) and two C. arabica cultivars (Palma II and Oeiras), used as rootstock. In experiment 2 (E2), the five C. canephora genotypes described, were cultivated on two types of seedlings (ungrafted and self grafted). Experimental design was factorial (5x2) and it was used the random block design, with five replicates. The genotypes Apoatã IAC3597-1A and Apoatã IAC3597-9B provide higher average uptake, translocation and nutrient use efficiency and they can be considered suitable choices for use as rootstocks.